Inflammatory bowel disease: towards a personalized medicine. (10th January 2018) - Flamant, Mathurin; Roblin, Xavier
The management of inflammatory bowel disease (IBD) has been transformed over the last two decades by the arrival of tumor necrosis factor (TNF) antagonist agents. Recently, alternative drugs have been approved, directed at leukocyte-trafficking molecules (vedolizumab) or other inflammatory cytokines (ustekinumab). New therapeutics are currently being developed in IBD and represent promising targets as they involve other mechanisms of action (JAK molecules, Smad 7 antisense oligonucleotide etc.). Beyond TNF antagonist agents, these alternative drugs are needed for early-stage treatment of patients with aggressive IBD or when the disease is resistant to conventional therapy. Personalized medicine involves the determination of patients with a high risk of progression and complications, and better characterization of patients who may respond preferentially to specific therapies. Indeed, more and more studies aim to identify factors predictive of drug response (corresponding to a specific signaling pathway) that could better manage treatment for patients with IBD. Once treatment has started, disease monitoring is essential and remote patient care could in some circumstances be an attractive option. Telemedicine improves medical adherence and quality of life, and has a positive impact on health outcomes of patients with IBD. This review discusses the current application of personalized medicine to the management of patients with IBD and the advantages and limits of telemedicine in IBD.